PENGARUH VARIASI KONSENTRASI ASETON TERHADAP PENINGKATAN DAYA, TORSI DAN EMISI MOTOR OTTO 4 LANGKAH : THE INFLUENCE OF ACETONE CONCENTRATION VARIATION ON POWER, TORQUE, AND EMISSIONS IN A 4-STROKE OTTO ENGINE - Reyhan Iwang Pratama; Hadi Rahmad; Ahsin Fahmi Mubarok (Mechanical Engineering Department Polinema Kediri, 2026)
This study investigates the effect of acetone addition to pertalite fuel on exhaust emissions and engine performance in a 150 cc four-stroke Otto engine. Acetone was blended at 1%, 3%, and 5% concentrations and tested using a dynamometer and gas analyzer. Results showed that 3% and 5% acetone mixtures significantly improved engine power and torque, with peak output at 9000 RPM. Emission analysis revealed reduced HC levels and increased CO₂, indicating more complete combustion. However, increased CO at 5% suggests a fuel-rich mixture. The 3% blend was considered the most balanced in enhancing performance while controlling emissions. This study highlights acetone's potential as an efficient and eco-friendly fuel additive.